Effect of Radiation Emitted by Wireless Devices on Male Reproductive Hormones: A Systematic Review - Maluin, Sofwatul Mokhtarah; Osman, Khairul; Jaffar, Farah Hanan Fathihah; Ibrahim, Siti Fatimah (Frontiers in Physiology, 2021)
Exposure to radiofrequency electromagnetic radiation (RF-EMR) from various wireless devices has increased dramatically with the advancement of technology. One of the most vulnerable organs to the RF-EMR is the testes. This is due to the fact that testicular tissues are more susceptible to oxidative stress due to a high rate of cell division and mitochondrial oxygen consumption. As a result of extensive cell proliferation, replication errors occur, resulting in DNA fragmentation in the sperm. While high oxygen consumption increases the level of oxidative phosphorylation by-products (free radicals) in the mitochondria. Furthermore, due to its inability to effectively dissipate excess heat, testes are also susceptible to thermal effects from RF-EMR exposure. As a result, people are concerned about its impact on male reproductive function. The aim of this article was to conduct a review of literature on the effects of RF-EMR emitted by wireless devices on male reproductive hormones in experimental animals and humans. According to the findings of the studies, RF-EMR emitted by mobile phones and Wi-Fi devices can cause testosterone reduction. However, the effect on gonadotrophic hormones (follicle-stimulating hormone and luteinizing hormone) is inconclusive. These findings were influenced by several factors, which can influence energy absorption and the biological effect of RF-EMR. The effect of RF-EMR in the majority of animal and human studies appeared to be related to the duration of mobile phone use. Thus, limiting the use of wireless devices is recommended.